Pharmacological and Genetic Inhibition of PD-1 Demonstrate an Important Role of PD-1 in Ischemia-Induced Skeletal Muscle Inflammation, Oxidative Stress, and Angiogenesis - Liu, Xiaoguang; Weng, Xinyu; Xiao, Weihua; Xu, Xin; Chen, Yingjie; Chen, Peijie (Frontiers in Immunology, 2021)
Angiogenesis is an important process under both physiological and pathophysiological conditions. Here we investigated the role and the underlying mechanism of PD-1 in hindlimb ischemia-induced inflammation and angiogenesis in mice. We found that inhibition of PD-1 by genetic PD-1 knockout or pharmacological PD-1 blocking antibodies dramatically attenuated hindlimb blood perfusion, angiogenesis, and exercise capacity in mice after femoral artery ligation. Mechanistically, we found that PD-1 knockout significantly exacerbated ischemia-induced muscle oxidative stress, leukocyte infiltration and IFN-γ production before abnormal angiogenesis in these mice. In addition, we found that the percentages of IFN-γ positive macrophages and CD8 T cells were significantly increased in P-1 knockout mice after hindlimb ischemia. Macrophages were the major leukocyte subset infiltrated in skeletal muscle, which were responsible for the enhanced muscle leukocyte-derived IFN-γ production in PD-1 knockout mice after hindlimb ischemia. Moreover, we demonstrated that IFN-γ significantly attenuated vascular endothelial cell proliferation, tube formation and migration in vitro. IFN-γ also significantly enhanced vascular endothelial cell apoptosis. In addition, the total number of TNF-α positive leukocytes/muscle weight were significantly increased in PD-1-/- mice after hindlimb ischemia. These data indicate that PD-1 exerts an important role in ischemia-induced muscle inflammation and angiogenesis.